Construction of an Hfr strain useful for transferring recA mutations between Escherichia coli strains. - Csonka, L N (1980)
Strain JC10240 (Hfr PO45 srlC300::Tn10 recA56 thr-300 ilv-318 rpsE300) was constructed. On account of the close linkage of Tn10 to recA56, the latter can be moved to other Escherichia coli (and closely related) strains in transductional or conjugational crosses selecting resistance to tetracycline.